The Bilangan Kromatik Lokasi Gabungan Graf Palem - Nurinsani, Aisyah; Welyyanti, Des; Yulianti, Lyra (Prodi Pendidikan Matematika Universitas Pesantren Tinggi Darul Ulum Jombang, 2024)
Vertex coloring of a graph is the coloring of vertices such that two adjacent vertices have different colors. The color code of a vertex is the distance from the vertex to the partition of the existing color set. A graph has a locating coloring if each vertex has a different color code. A palm graph is a graph constructed from a cycle graph, path graph, and star graph. A disjoint union of palm graphs is a disconnected graph with palm graphs as its components. The locating chromatic number of graph is the minimum colors of the graph to have locating coloring with k colors. In this paper, we determine the locating chromatic number of a disjoint union of palm graph.